LITERASI MATEMATIS SISWA ASPEK CONTENT SPACE AND SHAPE DI SMP NEGERI 02 SUNGAI RAYA - Parno, Muhamad; Sugiatno, Sugiatno; BS, Dian Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractMathematical literacy is an individual?s capacity to formulate, employ, and interpret mathematics in a variety of contexts. It includes reasoning mathematically and using mathematical concepts, procedures, facts, and tools to describe, explain, and predict phenomena. It assists individuals to recognise the role that mathematics plays in the world and to make the well-founded judgments and decisions needed by constructive, engaged and reflective citizens.This study aims to determine the level of students? mathematical literacy aspects of Content Space and Shape in junior high school 02 Sungai Raya. The answer in this study is to describe in detail in the form of a case study.The subjects of this study were 6 students of class IX A who were capable of upper, middle and lower with the object of their research mathematical literacy skills in the aspect of content space and shape in the three-dimensional materof cubes and beams. The results of the research on class IX A students showed that the two top-capable students were able to reach level 6 mathematical literacy aspects of content space and shape, two middle-capable students were able to reach level 3 mathematical literacy aspects of content space and shape, one lower-capable student was able to reach level 3 mathematical literacy aspect of content space and shape, and one lower-capable student is able to reach level 2 mathematical literacy aspects of content space and shape. This result implies that there are students who are able to reach above level 2 mathematical literacy aspects of space and shape content.Keyword:Mathematical Literacy, Level of Mathematical Literacy, Content Space and Shape